2020
DOI: 10.1111/bjet.12977
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on the effects of gamified cooperation and competition on English vocabulary learning

Abstract: Gamification has become a popular approach to blending learning with fun and enjoyable experiences. However, gamification research has been criticized for mostly focusing on game mechanics and related outcomes while paying little attention to the psychological processes that mediate the relationship between these mechanics and outcomes. Furthermore, the majority of existing gamification studies have focused on competitive game features. Thus, the full potential of cooperative gamification has yet to be explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 53 publications
4
73
0
Order By: Relevance
“…Most importantly, the findings of the study show that educational games that were employed once should not be used again within a week, because they will feel bored and will not participate every day. This finding is confirmed by (Dindar et al 2021) who focused on using games only once to teach the students. By using educational games, the students can improve their engagement, memorize new words, and as well as explain the new words.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Most importantly, the findings of the study show that educational games that were employed once should not be used again within a week, because they will feel bored and will not participate every day. This finding is confirmed by (Dindar et al 2021) who focused on using games only once to teach the students. By using educational games, the students can improve their engagement, memorize new words, and as well as explain the new words.…”
Section: Discussionmentioning
confidence: 55%
“…In this regard, while reading readers can often communicate with the texts as they can derive the meaning by using different kinds of information, such as bottom-up processing and top-down processing. Dindar et al (2021) also indicated that reading aims to obtain correct information from a reading background that the writer intended to attain from the reader. Li and Cummins (2019) argued that reading creativity can be described as an intellectual skill a person can use when engaging with the circumstance they are reading.…”
Section: Definition Of Reading Comprehensionmentioning
confidence: 99%
“…Some studies found differences in motivation in the short and long term and by the complexity of tasks that have to be performed. Dindar et al [37] and Katz-Navon and Erez [38] both suggest that a DGBLsetting collaboration invokes higher task effort in long-lasting learning activities compared with competition, and Chen [39] reports that collaboration increases reflective thinking and effective problem-solving. Therefore, collaboration seems to be an effective feature for higher and complex learning tasks that takes a longer time period to carry out.…”
Section: Competition and Collaboration In Digital Game Based Learningmentioning
confidence: 99%
“…Its effectiveness depends on the quality of dialogues in acquiring knowledge from each other by questioning, answering, and discussing [18,41]. These discussions, about conflicting information, lead to opportunities for reflection on the offered content and present knowledge [13], and thus stimulate information exchange and constructive communication [37]. To be more specific: When asking questions, participants outline what they know and/or identify what they need to know, which helps to become aware of their knowledge and to generate knowledge.…”
Section: Collaborationmentioning
confidence: 99%
See 1 more Smart Citation